The Relationship between Green Human Resource Management Practices and Environmental Performance in Sarawak - Kiew, Bonnie SW; Mohd Nor, Norasmiha; Sabtu, Hilyati (Research in Management of Technology and Business, 2025)
Green human resource management (GHRM) can be defined as an approach that enables an organisation to increase its environmental performance. Green human resource management is here to encourage employees to become more alert about the environment. Besides, GHRM motivates the employees’ responsibility toward the environment and team spirit. Human resource management as a strategic tool by engaging talented individuals with special green skills and knowledge can achieve green environment goals. The purpose of the study is to examine the level of green human resource management practices, to understand the level of environmental performance, and to identify the relationship between green human resource management practices and environmental performance. The target respondents were selected and covered mainly by the employees in manufacturing companies, which is 384 respondents based on 137,700 population calculated from Krejcie and Morgan. The research utilised a quantitative method. The data will be analysed by using the Statistical Package for Social Science (SPSS) version 25. The results of this study are expected to understand the relationship between GHRM practices and environmental performance in manufacturing companies in Sarawak.